2013
DOI: 10.1021/ac400915z
|View full text |Cite
|
Sign up to set email alerts
|

The Observation of Dianions Generated by Electrochemical Reduction of trans-Stilbenes in Ionic Liquids at Room Temperature

Abstract: Three highly aprotic bis(trifluoromethylsulfonyl)amide (NTf2(-)) based ionic liquids (ILs) containing the cations trihexyl(tetradecyl)phosphonium (P6,6,6,14(+)), N-butyl-N-methylpyrrolidinium (Pyrr4,1(+)), and (trimethylamine)(dimethylethylammine)dihydroborate ((N111)(N112)BH2(+)) have been examined as media for room temperature voltammetric detection of highly basic stilbene dianions electrochemically generated by the reduction of trans-stilbene (t-Stb) and its derivatives (4-methoxy-, 2-methoxy-, 4,4'-dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(55 citation statements)
references
References 29 publications
(57 reference statements)
9
45
0
Order By: Relevance
“…The large ΔEp could be explained by the uncompensated resistance, assuming reversible electron transfers (keeping the ΔE12° value small). The increase in stability of very basic dianions in RTIL at higher substrate concentrations was also reported by Abdul-Rahim et al, 26 for the voltammetry of trans-stilbene in another NTf2 RTIL. The chemical irreversibility of the wave was attributed to the reaction of the stilbene dianion with trace water.…”
Section: Cyclic Voltammetry and Spectroelectrochemistry In Bmimntf2supporting
confidence: 81%
“…The large ΔEp could be explained by the uncompensated resistance, assuming reversible electron transfers (keeping the ΔE12° value small). The increase in stability of very basic dianions in RTIL at higher substrate concentrations was also reported by Abdul-Rahim et al, 26 for the voltammetry of trans-stilbene in another NTf2 RTIL. The chemical irreversibility of the wave was attributed to the reaction of the stilbene dianion with trace water.…”
Section: Cyclic Voltammetry and Spectroelectrochemistry In Bmimntf2supporting
confidence: 81%
“…It was found that Y 2 -naph is the strongest reducing agent while Y 2 -anth is the weakest, with Y 2 -stilbene being in the middle of the series. This series parallels the reduction potential of the bridging arenes in the free form (Abdul-Rahim et al, 2013;Connelly and Geiger, 1996). Consequently, the reaction of Y 2 -stilbene and 2,2′-bipyridine (bipy) or phenylacetylene (PhCCH) resembled the reactivity of As remarked in this section, group 3 metals prefer binding to the central C-C bond rather than an aromatic ring as observed for uranium (Diaconescu and Cummins, 2012).…”
Section: Group 3 Metal Stilbene Complexessupporting
confidence: 61%
“…[5][6][7] Hence, the most active field in electrochemistry, together with RTILs, is currently focused on electrodeposition, [8][9][10] supercapacitors, 11 batteries, [12][13][14] and the study of the heterogeneous electron transfer of electroactive organic compounds in RTILs. [15][16][17][18][19][20][21] It is important to note that the ''stabilization'' of radicals and radical anions has been observed in few cases (such as nitroderivatives, 15,16 halogenated compounds, 22,23 acetophenone, 24 stilbene, 25 and superoxide ions 26 ). Following this approach, it is possible to determine the electrocatalytic properties of some RTILs, understanding as electrocatalytic properties the fact that the same reduction or oxidation process can take place at a lower potential value depending on the composition of the RTILs.…”
Section: Introductionmentioning
confidence: 99%